Development of Antimicrobial Nitric Oxide-Releasing Fibers - Daniel C. Wang; Justin R. Clark; Richard Lee; Adam H. Nelson; Anthony W. Maresso; Ghanashyam Acharya; Crystal S. Shin (MDPI AG, 2021)
Nitric oxide (NO) is a highly reactive gas molecule, exhibiting antimicrobial properties. Because of its reactive nature, it is challenging to store and deliver NO efficiently as a therapeutic agent. The objective of this study was to develop NO-releasing polymeric fibers (NO-fibers), as an effective delivery platform for NO. NO-fibers were fabricated with biopolymer solutions of polyvinyl pyrrolidone (PVP) and ethylcellulose (EC), and derivatives of N-diazeniumdiolate (NONOate) as NO donor molecules, using an electrospinning system. We evaluated in vitro NO release kinetics, along with antimicrobial effects and cytotoxicity in microorganisms and human cell culture models. We also studied the long-term stability of NONOates in NO-fibers over 12 months. We demonstrated that the NO-fibers could release NO over 24 h, and showed inhibition of the growth of Pseudomonas aeruginosa (P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA), without causing cytotoxicity in human cells. NO-fibers were able to store NONOates for over 12 months at room temperature. This study presents the development of NO-fibers, and the feasibility of NO-fibers to efficiently store and deliver NO, which can be further developed as a bandage.